การจัดการท่องเที่ยวโดยชุมชนในพื้นที่ลุ่มน้ำทะเลสาบสงขลา : กรณีศึกษา ตำบลเกาะหมาก อำเภอปากพะยูน จังหวัดพัทลุง: Community-based Tourism Management in the Songkhla Lake Basin : Case Study Koh Mak, Pak Phayun District, Phatthalung Province - Wisuttinee Taneerat, วิสุทธิณี ธานีรัตน์ (SOCIAL SCIENCES RESEARCH AND ACADEMIC JOURNAL, 2021)
การศึกษาเรื่องนี้มีวัตถุประสงค์ 1) เพื่อศึกษารูปแบบการจัดการท่องเที่ยวโดยชุมชนในพื้นที่ลุ่มน้ำทะเลสาบสงขลาของชุมชนเกาะหมาก อำเภอปากพะยูน จังหวัดพัทลุง และ 2) เพื่อศึกษาแนวทางการพัฒนาการจัดการท่องเที่ยวของชุมชนเกาะหมาก อำเภอปากพะยูน จังหวัดพัทลุง งานวิจัยนี้เป็นวิจัยเชิงคุณภาพ โดยใช้วิธีการเจาะจงเลือกผู้ที่มีส่วนเกี่ยวข้องกับการจัดการท่องเที่ยวโดยชุมชนในพื้นที่ลุ่มน้ำทะเลสาบสงขลา สามารถแบ่งกลุ่มผู้ให้ข้อมูลหลักออกเป็น 4 กลุ่ม ประกอบด้วย หน่วยงานภาครัฐ ผู้นำชุมชน ผู้ประกอบการ และผู้มีส่วนได้ส่วนเสียในการท่องเที่ยวของชุมชนเกาะหมาก รวมจำนวน 30 คน ใช้การสัมภาษณ์กึ่งมีโครงสร้าง และการสังเกตแบบไม่มีส่วนร่วมในการรวบรวมข้อมูลจากกลุ่มเป้าหมาย วิเคราะห์ข้อมูลโดยการสรุปประเด็น และนำไปสู่การวิเคราะห์เนื้อหาสาระ (Content Analysis) ผลการศึกษาพบว่า 1) ชุมชนเกาะหมาก อำเภอปากพะยูน ตั้งอยู่ในพื้นที่ลุ่มน้ำทะเลสาบสงขลามีทรัพยากรทางธรรมชาติที่เป็นทรัพยากรการท่องเที่ยวโดดเด่นอย่างหลากหลาย ทั้งทางบกและทางทะเล รวมทั้งมีแหล่งเที่ยวทางวัฒนธรรมและภูมิปัญญา จึงสามารถดึงดูดนักท่องเที่ยวที่สนใจเป็นจำนวนมาก สำหรับลักษณะการจัดการท่องเที่ยวเป็นความร่วมมือที่เกิดขึ้นโดยคนในชุมชน ซึ่งผลจากการจัดการท่องเที่ยวของชุมชนเกาะหมาก ทำให้เกิดประโยชน์ต่อชุมชนที่สำคัญ 3 ด้าน ได้แก่ ด้านการสร้างงานและสร้างรายได้ ด้านความเข้มแข็งของชุมชนและพึ่งตนเอง และด้านการท่องเที่ยวในชุมชน 2) แนวทางการพัฒนาการจัดการท่องเที่ยวของชุมชนเกาะหมาก หน่วยงานที่เกี่ยวข้องควรให้การสนับสนุนด้านการผลิตและด้านการตลาด โดยเฉพาะการออกแบบผลิตภัณฑ์และการทำการตลาดออนไลน์ This study aimed 1) to study the characteristic of community-based tourism management in the Songkhla lake basin area of the Koh Mak community, Pak Phayun District, Phatthalung Province. And 2) to study the guideline for development tourism management of the Koh Mak community. This research was a qualitative research. By using a specific method to select those involved in the management of community-based tourism in the Songkhla Lake Basin. The key informants were divided into 4 groups: government agencies, community leaders, entrepreneurs and tourism stakeholders of the Koh Mak community, totaling 30 people. The researcher used a semi-structured interview and observations without participation in collecting data from the target audience. Then, analyze the data by summarizing the issues and lead to content analysis. The result found that 1) Koh Mak Community, Pak Phayun District located in the Songkhla lake basin, it had a wide variety of natural resources that are outstanding tourism resources both by land and by sea as well as having cultural and wisdom tourism sites, thus able to attract a lot of interested tourists. For the characteristic of tourism management was a cooperation made by people in the community. The effects of tourism management of the Koh Mak community affected in three important benefits to the community: job creation and income generation, the strength of the community and self-reliance, and tourism in the community. 2) The guidelines for development tourism management of the Koh Mak community, the relevant government should support production and marketing especially for product design and online marketing.